LEMBAR KERJA PESERTA DIDIK BERBASIS CABRI 3D UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA - Benny Hendriana (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2019)
The research aims to develop a Worksheet with Cabri 3D that is able to improve students' conceptual understanding. This study uses a Research and Development model. This research was conducted at Gameel Akhlaq IT Middle School. The results of the initial validation from experts and practitioners, the feasibility aspect of the content has an average of 85.32% or can be categorized very well. In this aspect, the material in the LKPD is in accordance with SK and KD. For the feasibility aspect, presentation has an average of 83.93% in the excellent category. In the presentation aspect, LKPD is complete and supports the improvement of understanding of concepts. For aspects of language assessment has an average of 81.41% in the good sagat category. In the aspect of language assessment LKPD is communicative, in accordance with the level of development of students, integration of thinking paths, and use of terms, symbols or icons.